Bouches béantes et voix blanches dans le théâtre de Howard Barker - Vanasay Khamphommala (Sillages Critiques)
This paper explores the ambiguous treatment of vocality in the work of Howard Barker, whose theatre appears as an attempt to conjure up the voice of the dead. By comparing his plays and his paintings, it strives to underline the paradoxical function of the mouth in Barker’s imagination, where it functions both as a sign of and an obstacle to the emergence of the voice. The paper then analyses how the playwright delineates an imaginary and ideal voice that stands in contrast to both lyricism and banality in language. If this ideal voice is to be heard, theatre must first create an empty space in which it can resonate: it is this process of emptying out that is finally examined, on the page, on the stage, in the actor.